Sociological research methodology in the media sphere - Altynbek Д.Н.; Serdali Б.К.; Nuskabaev О.Н. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The article summarizes the views on the current socio-political, cultural and economic situation in the context of sociological research in journalism. The study is aimed at analyzing the views of young people on what traditional religions they follow, the level of their religious knowledge and what they should do against the activities of non-traditional religious movements and religious extremist organizations and their destructive activities. The article, written using research methods such as pilot studies, rapid surveys, focus group interviews, uses the method of multistage random sampling of sociology in journalism. Quantitative and qualitative approaches to data collection have been implemented. The methods were used to organize and use focus groups, store, process, compare statistics, use the results in media research, select new methods and queries. The effectiveness of sociological research, the choice of respondents, open and closed types, survey methods (questionnaires, content analysis, expert interviews, in-depth interviews, telephone interviews, etc.) are considered. The goals and objectives of content analysis in the media are also clearly formulated. Methods used were social media polls, selective placement by industry, and random polls. The problems of sociological research (organization, planning, recognition of social reality) in the work of the editorial board were not left aside.